Analysis of Experimental Studies on the Reinforcement of Reinforced Concrete Columns with Polymer Composite Materials - Akramov Khusnitdin Akhrarovich; Davlyatov Shohrukh Muratovich; Kimsanov Bakhromjon Ikromjon ogli; Nazirov Ayubkhon Sultonjon ogli (Peerian Journals Publishing, 2022)
The problem of collecting, analyzing and systematizing experimental information on the testing of reinforced concrete structures reinforced with polymer composite materials is considered. It is noted that these data are scattered over a large number of publications, which makes their use difficult. Therefore, the creation of databases based on the results of experimental studies of reinforced structures is an important task. Only 3 books have been written on this problem in Russian, and two of them are based on the results of foreign studies. It is noted that the vast majority of other publications present general ideas about the reinforcement of reinforced concrete structures with the help of polymer composite materials, the technology of gluing composites, a number of works describe methods for calculating reinforced concrete structures reinforced with composite materials using the limit state method without justification. Next, the results of domestic experiments on the behavior of reinforced concrete structures reinforced with polymer composite materials under static loading are considered. It is concluded that many domestic publications do not always provide complete and systematized information on the deformation of reinforced concrete structures reinforced with polymer composite materials, on test conditions, but only data on the magnitude of breaking loads for some reinforcement schemes. Then the results of a number of correct experiments on the behavior of reinforced concrete structures are presented, with an analysis that differs from that done by the authors of the experimental studies
Keywords: reinforced concrete columns; gain; fiber reinforced plastic; carbon fiber